(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is dedicated to philosophy of psychologism on the basis of the Japanese art: literature and cinematography. Stories of Ryunosuke Akutagawa and films of Akira Kurosawa and Takeshi Kitano are the subject of analysis. The article focuses of master peculiarities of phychologism in literature, its literary and cinematographic devices, such as a stream of consciousness, self-analysis, eye play, omission, psychology of speechless emotions, blending in the nature, and others. Special attention is given to the uniqueness of the Japanese culture in its artistic expression. The article demonstrates the difference between literature and film-image of the characters’ inner world and means of expression of their psychological condition. Key words: Japanese culture, Japanese art, psychologism, devices of psychologism in literature, psychological condition of a character, film.